2020
DOI: 10.1108/jeas-11-2018-0131
|View full text |Cite
|
Sign up to set email alerts
|

Employees' commitment to change: personality traits and organizational culture

Abstract: PurposeThis study examines the influences of personality traits on the employees' commitment to change that moderated by the organizational culture. The employee's commitment to change is important for the large companies to sustain in the global economy.Design/methodology/approachThe quantitative data were collected from the employees in the large companies that are listed in Bursa Saham Kuala Lumpur (BSKL) Malaysia. The research used a simple random sampling and a cross-sectional survey.FindingsThe results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 93 publications
1
13
0
Order By: Relevance
“…For instance, aversive leadership, tyrannical leadership, etc. Researches have also taken into account the impact of C2C on various variables including employee psychological processes (Straatmann et al, 2018), supportive intentions (Straatmann et al, 2018), organizational identification (Zappal a et al, 2019), change efficacy (Wulandari et al, 2019), employee innovativeness, personality traits (Marchalina et al, 2018), etc. Future researchers can look for other variables that are impacted by the C2C.…”
Section: Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, aversive leadership, tyrannical leadership, etc. Researches have also taken into account the impact of C2C on various variables including employee psychological processes (Straatmann et al, 2018), supportive intentions (Straatmann et al, 2018), organizational identification (Zappal a et al, 2019), change efficacy (Wulandari et al, 2019), employee innovativeness, personality traits (Marchalina et al, 2018), etc. Future researchers can look for other variables that are impacted by the C2C.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…, 2019), change efficacy (Wulandari et al. , 2019), employee innovativeness, personality traits (Marchalina et al. , 2018), etc.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…On the other hand, it is noteworthy that the openness to experience trait has a statistically insignificant relationship with customer citizenship behaviours (Lakmali and Kajendra, 2021). In large Malaysian companies, organizational culture moderates the association between employees' commitment to change and personality traits (Marchalina et al. , 2021).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Meanwhile, Marchalina, Ahmad, & Gelaidan (2020) in their research related to Commitment to Change in Malaysia used the personality trait variable as a predictor and the Organizational Culture variable as a moderator. From the test, it was found that personality traits had a significant effect on the Commitment to Change by being mediated by Organizational Culture (6). Acar (2012) in research on employee enthusiasm to ensure that the outcomes that continue to affect the Commitment to Change.…”
Section: The Influence Of Organizational Culture On Employee Affectiv...mentioning
confidence: 99%
“…Recent studies have proven the importance of employee attitude factors in determining the success of the organizational change. Lack of commitment and resistance (rejection) are real barriers to change (5) because employees are a major role in organizational change (6). According to Brzeziński and Bąk (2015) employees are a crucial factor in all changes because without involving employees, changes and innovations will not be able to be made.…”
Section: Introductionmentioning
confidence: 99%